Simulated air dives induce superoxide, nitric oxide, peroxynitrite, and Ca2+ alterations in endothelial cells - Wang, Q.; Guerrero, F.; Lambrechts, K.; Mazur, A.; Buzzacott, Peter; Belhomme, M.; Theron, M. (SPRINGER, 2020)
Human diving is known to induce endothelial dysfunction. The aim of this study was to decipher the mechanism of ROS production during diving through the measure of mitochondrial calcium concentration, peroxynitrite, NO°, and superoxide towards better understanding of dive-induced endothelial dysfunction. Air diving simulation using bovine arterial endothelial cells (compression rate 101 kPa/min to 808 kPa, time at depth 45 min) was performed in a system allowing real-time fluorescent measurement. During compression, the cells showed increased mitochondrial superoxide, peroxynitrite, and mitochondrial calcium, and decreased NO° concentration. MnTBAP (peroxynitrite scavenger) suppressed superoxide, recovered NO° production and promoted stronger calcium influx. Superoxide and peroxynitrite were inhibited by L-NIO (eNOS inhibitor), but were further increased by spermine-NONOate (NO° donor). L-NIO induced stronger calcium influx than spermine-NONOate or simple diving. The superoxide and peroxynitrite were also inhibited by ruthenium red (blocker of mitochondrial Ca2+ uniporter), but were increased by CGP (an inhibitor of mitochondrial Na+-Ca2+ exchange). Reactive oxygen and nitrogen species changes are associated, together with calcium mitochondrial storage, with endothelial cell dysfunction during simulated diving. Peroxynitrite is involved in NO° loss, possibly through the attenuation of eNOS and by increasing superoxide which combines with NO° and forms more peroxynitrite. In the field of diving physiology, this study is the first to unveil a part of the cellular mechanisms of ROS production during diving and confirms that diving-induced loss of NO° is linked to superoxide and peroxynitrite.